2017
DOI: 10.1371/journal.pone.0171944
|View full text |Cite
|
Sign up to set email alerts
|

Subunit vaccine candidates against Aeromonas salmonicida in rainbow trout Oncorhynchus mykiss

Abstract: Aeromonas salmonicida subsp. salmonicida is the etiological agent of furunculosis and a major fish health problem in salmonid aquaculture worldwide. Injection vaccination with commercial mineral oil-adjuvanted bacterin vaccines has been partly successful in preventing the disease but in Danish rainbow trout (Oncorhynchus mykiss, Walbaum) aquaculture furunculosis outbreaks still occur. In this study we tested the efficacy of experimental subunit vaccines against A. salmonicida infection in rainbow trout. We uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 70 publications
1
21
0
Order By: Relevance
“…Comparing with mortality data in Table 2, the vaccinated group shows the lowest mortality percentages, as well as the antibody titers data (Figure 1). This result same to Villumsen et al (2012); Romstad et al (2013); Marana et al (2017) that stated if antibody titers are related to survival rate between unvaccinated fish and vaccinated fish.…”
Section: Discussionsupporting
confidence: 81%
“…Comparing with mortality data in Table 2, the vaccinated group shows the lowest mortality percentages, as well as the antibody titers data (Figure 1). This result same to Villumsen et al (2012); Romstad et al (2013); Marana et al (2017) that stated if antibody titers are related to survival rate between unvaccinated fish and vaccinated fish.…”
Section: Discussionsupporting
confidence: 81%
“…Nowadays, however, immunoinformatics is also applied toward the CTL epitopes for designing vaccines against the pathogens of fish (Barbedo, 2014). Published data showed that the designed CTL epitopes are successful in neutralizing the pathogens of fish such as Aeromonas sp., Edwardsiella tarda, and Flavobacterium columnare (Mahendran et al, 2016;Marana et al, 2017). Among the top five epitopes predicted in the current study, only the epitope 98 TVTAPRTDP 106 , having all the necessary properties of a probable candidate vaccine against WSSV scored a value of 1.000, in terms of antigenicity.…”
Section: Discussionmentioning
confidence: 75%
“…The experimental data of cord and tilapia reported to have both MHC class I and class II molecules for initiating immune responses against pathogens. Hence, the peptide that can target HLA-A*0201, HLA-B*3501, and HLA-B*3508 with excellent binding abilities, could be used as effective vaccines against selective fish pathogens (Grimholt, 2016;Mahendran, Jeyabaskar, Sitharaman, Michael, & Paul, 2016;Marana et al, 2017). Recently, in-silico approach was successfully used to predict epitopes, having strong immunogenicity against Streptococcus agalactiae, Edwardsiella tarda, and Flavobacterium columnarie: three pathogenic bacteria that cause streptococcosis, edwardsiellosis and columnaris in fish, respectively (Mahendran et al, 2016;Pereira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…First of all, it may be relevant to include other immunogenic recombinant proteins common for all serotypes together with #10. Secondly, the antigen concentration in fish vaccine preparations is known to play a significant role for protection (Marana, Jorgensen, Skov, Chettri, Mattsson, Dalsgaard, Kania, & Buchmann, ), which calls for additional dose–response studies with regard to this subunit vaccine. In conclusion, the parasite protein #10, which was tested in the present study, was shown to confer protection and elicit an antibody response.…”
Section: Discussionmentioning
confidence: 99%